2017
DOI: 10.1159/000477777
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection after Hepatectomy for Hepatocellular Carcinoma

Abstract: Aims: To clarify the clinical impact, risk factors, and preventive methods for surgical site infection (SSI) after hepatectomy for hepatocellular carcinoma (HCC). Methods: We included 879 consecutive patients who underwent hepatectomy for HCC between 2002 and 2011. Univariate and multivariate analyses were conducted to identify the risk factors for incisional and organ/space SSIs. ORs and 95% CIs are reported. Results: The incidences of incisional and organ/space SSIs were 24 (2.7%) and 73 (8.3%), respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Surgical site infection (SSI) is a common complication following hepatectomy and is classified as superficial SSI, deep or incisional SSI, and organ/space SSI . Organ/space SSI and intra‐abdominal infection (IAI) are lethal complications following hepatectomy, and previous studies have shown that the incidence of IAI following hepatectomy may reach 17% . IAI is associated with poor long‐term outcomes in patients with both primary and secondary malignancies following hepatectomy .…”
Section: Introductionmentioning
confidence: 99%
“…Surgical site infection (SSI) is a common complication following hepatectomy and is classified as superficial SSI, deep or incisional SSI, and organ/space SSI . Organ/space SSI and intra‐abdominal infection (IAI) are lethal complications following hepatectomy, and previous studies have shown that the incidence of IAI following hepatectomy may reach 17% . IAI is associated with poor long‐term outcomes in patients with both primary and secondary malignancies following hepatectomy .…”
Section: Introductionmentioning
confidence: 99%
“…Surgical indications, preoperative treatment and surgical operations have an impact on the occurrence of bile leakage. In a retrospective analysis of 879 patients who underwent hepatectomy, Chikara et al found that bile leakage was the strongest risk factor for a postoperative organ (or lacunar) infection [ 33 ], so, bile leakage leads to poor drainage of infectious bile, which leads to cholestasis and secondary infection [ 34 ]. Therefore, the operator should strictly follow the operating procedures and handle the operation with care, and in case of accidental injury, it must be treated immediately.…”
Section: Discussionmentioning
confidence: 99%
“…The infection rate of our study was 8.2%, including 6.5% of SSI and 2.0% of RI, which were close to reported results. Previous studies reported infection rate after hepatectomy as 2.1% to 34% 15,23,24 . We considered possible reasons of different infection rates in previous studies as follows: first, several studies enrolled patients with multiple diseases, including liver metastasis and hepatolithiasis.…”
Section: Discussionmentioning
confidence: 99%